Jobco Digital Module to Improve Student Learning Outcomes - Sulikah Sulikah; Heri Pratikto; Wening Patmi Rahayu (International Journal of Education, Language, Literature, Arts, Culture, and Social Humanities, 2024)
This research aims to develop a product in the form of a digital module with the Canva platform and flipbook maker to improve student learning outcomes in cost accounting courses on the topic of cost of orders. Digital modules make it easy for students to access and increase students' interest in learning. This development research uses the ADDIE research design and development model. The research results found that the feasibility level in terms of media was very good with a score of 94%, while in terms of feasibility the digital module material developed received a score of 95% with very feasible criteria. The effectiveness results show that the digital module is able to improve student learning outcomes on the topic of cost of goods ordered. Educators are required to be creative in developing teaching materials, so digital modules are a form of creativity in teaching materials by presenting audio, visuals, animation and flexibility in use.